2018
DOI: 10.1002/jcp.26596
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐224 suppresses osteoblast differentiation by inhibiting SMAD4

Abstract: Osteoblast differentiation was found to be regulated by a variety of cell signaling and intracellular regulatory factors. In this study, we aimed at investigating the regulatory effect of microRNA-224 on osteoblast differentiation and its molecular mechanism. Expression of miR-224 in the osteoblasts, adipose-derived mesenchymal stem cells (MSC-A), bone marrow-derived mesenchymal stem cells (MSC-B) and mbilical cord-derived mesenchymal stem cells (MSC-U) were detected using RT-PCR. Expression of miR-224 was low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…31 The Smad4 complex transcribes Runx2 and interacts with Runx2 to initiate the expression of other osteoblast genes. 32 Thus, Smad4 expression is mediated by Smad4/Runx2 signaling at the transcriptional level, and Smad4 regulates Runx2 activity and the expression of other osteoblast genes in a feedback loop. 33,34 The cytoskeleton has been shown to control the activation of Smad4/Runx2 signaling in mesenchymal cells upon external stimulation, and cell morphology remodeling and cytoskeletal organization can affect stem cell lineage commitment.…”
Section: Introductionmentioning
confidence: 99%
“…31 The Smad4 complex transcribes Runx2 and interacts with Runx2 to initiate the expression of other osteoblast genes. 32 Thus, Smad4 expression is mediated by Smad4/Runx2 signaling at the transcriptional level, and Smad4 regulates Runx2 activity and the expression of other osteoblast genes in a feedback loop. 33,34 The cytoskeleton has been shown to control the activation of Smad4/Runx2 signaling in mesenchymal cells upon external stimulation, and cell morphology remodeling and cytoskeletal organization can affect stem cell lineage commitment.…”
Section: Introductionmentioning
confidence: 99%
“…But another study in three types of cells (MC3T3-E1 cells, mouse and human BMSCs), miR-98-5p inhibited osteogenic differentiation by targeting HMGA2 (Zheng et al, 2019). And for miR-224, it inhibited osteoblast differentiation in mesenchymal stem cells by directly targeting Smad4 (Luo et al, 2018), but miR-224 regulated the expression of Rac1 to promoted osteogenic differentiation in human mesenchymal stem cells (Cai et al, 2019).…”
Section: Mirnas Regulate Other Factors In Osteoblastsmentioning
confidence: 97%
“…Similarly, a previous study indicated that exposure to elevated phosphorus levels results in the upregulation of Runx2 expression and ALP activity ( 18 ). Runx2 is a notable transcription factor in the process of VSMC osteo-/chondrogenic transdifferentiation, which induces the expression of major bone matrix components, including type I collagen ( 5 ), osteocalcin ( 19 ) and OPN ( 20 ). Runx2 can be transcribed from the distal P1 promoter or the P2 promoter, resulting in the expression of two different subtypes (Runx2 I and II), which can be expressed in ossified and cartilage cells; both subtypes exhibit similar features in chondrocytes and osteoblasts.…”
Section: Discussionmentioning
confidence: 99%